(3GdETGQI GdhajI Edi GdNUhUjGJ GdCTQajIs - (3GdHgGA GdHGYhfj , eMeO Hf jhSa Hf CMeO GdHgGA GdHGYhfj, HgGA GdOjf,J (B916 (3g` s
(3ChdgG (B:s
(3jbhd CabQ GdhQi Edi GdgOi eMeO Hf jhSa Hf CMeO jYRi Edi HGYhf efg GdfSH hddCeGe GdTGaYi GdePgH s
(3BNQgG (B:s
(3hVefJ HQGYI GdcdGe HeG jahb GdeSc ai GdNJGe s
(3hgj CQLhRI ai HQSHGi Gdedc GdCTQas
(3PcQ ajgG GdfGXe Gf dYeg TeS GdOjf GQLhRI GQN ajgG ddNdaGA hNJegG HGdGTQa HQSHGi aPjd GdeUfa YdjgG HGf PcQ ajgG GdbGFejf HGdGeQ HYO ef PcQge Yegs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B155 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B121s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe LRA(B2/ 1 - (3U (B18 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs